2017
DOI: 10.1111/jfbc.12392
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of brown seaweed polysaccharides (BSP) as prebiotics and potential immunomodulators

Abstract: Prebiotics enhance immune response through the modulation of intestinal microbial activities, production of short chain fatty acids (SCFA), direct interaction with toll‐like receptors and mucin production. These non‐digestible food components are known to be resistant to enzymatic hydrolysis by digestive enzymes and are utilized as carbon source for the growth of beneficial bacteria population through the process of fermentation. Brown seaweed polysaccharides (BSP) have been described as emerging prebiotics du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 83 publications
2
52
0
Order By: Relevance
“…The data that support the findings of this study are openly available in Web of Science at https://doi.org/10.1016/j.ijbiomac.2018.01.183. Figure 2 (Okolie et al, 2017). The data that support the findings of this study are openly available in Web of Science at https://doi.org/10.1111/jfbc.12392 (Shang et al, 2017).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The data that support the findings of this study are openly available in Web of Science at https://doi.org/10.1016/j.ijbiomac.2018.01.183. Figure 2 (Okolie et al, 2017). The data that support the findings of this study are openly available in Web of Science at https://doi.org/10.1111/jfbc.12392 (Shang et al, 2017).…”
Section: Resultssupporting
confidence: 64%
“…Figure (Okolie et al , ). The data that support the findings of this study are openly available in Web of Science at https://doi.org/10.1111/jfbc.12392 (Shang et al , ).…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the administration of fucoidan derived from Wakame seaweed to mice enhanced NK activity in herpes simplex virus type 1‐infected mice (Hayashi, Nakano, Hashimoto, Kanekiyo, & Hayashi, ). Although it is unclear which component contributed to the increase in the number of NK cells in this study, immunity was activated not only by fucoidan but also by other polysaccharides derived from seaweed (Okolie, Ck Rajendran, Udenigwe, Aryee, & Mason, ; Shi et al, ), and it is possible that either of these was involved in the increase of NK cells. A decrease in neutrophils was observed in Experiment 3.…”
Section: Discussionmentioning
confidence: 71%
“…Epidemiological and experimental data suggest that a fiber-rich diet can help to reduce appetite and induce gut microbiota to produce compounds that can reduce the diet-induced risk of metabolic disorders (Thorburn et al, 2015;Trompette et al, 2014). For example, supplementation with DFs alters the composition of gut bacteria populations and the associated expression of genes involved in aerobic fermentation and short-chain fatty acid (SCFA) generation (Okolie, Rajendran, Udenigwe, Aryee, & Mason, 2017;Wu et al, 2011).…”
mentioning
confidence: 99%